2023
DOI: 10.1002/iid3.1121
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the theranostic potentials of miRNA and epigenetic networks in autoimmune diseases: A comprehensive review

Sagnik Nag,
Oishi Mitra,
Garima Tripathi
et al.

Abstract: BackgroundAutoimmune diseases (AD) are severe pathophysiological ailments that are stimulated by an exaggerated immunogenic response towards self‐antigens, which can cause systemic or site‐specific organ damage. An array of complex genetic and epigenetic facets majorly contributes to the progression of AD, thus providing significant insight into the regulatory mechanism of microRNA (miRNA). miRNAs are short, non‐coding RNAs that have been identified as essential contributors to the post‐transcriptional regulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 230 publications
(440 reference statements)
0
3
0
Order By: Relevance
“…MiRNAs orchestrate a complex interplay by targeting the key genes involved in immune modulation, gut microbial homeostasis, epithelial barrier function, and cytokine signaling [ 76 ]. This nuanced regulatory network positions miRNAs as promising candidates not only in understanding the pathogenesis of IBD but also in unraveling their potential role in the development of resistance to therapeutic interventions [ 77 ].…”
Section: Epigenetic Modificationsmentioning
confidence: 99%
“…MiRNAs orchestrate a complex interplay by targeting the key genes involved in immune modulation, gut microbial homeostasis, epithelial barrier function, and cytokine signaling [ 76 ]. This nuanced regulatory network positions miRNAs as promising candidates not only in understanding the pathogenesis of IBD but also in unraveling their potential role in the development of resistance to therapeutic interventions [ 77 ].…”
Section: Epigenetic Modificationsmentioning
confidence: 99%
“…The diagnosis and treatment of ADs, especially of rare diseases such as SSc, are often hampered by challenges due to the complexity of the identification of initial symptoms; the poor knowledge of the disease; and the lack of rapid, accurate, and universally recognized diagnostic markers. Therefore, in recent years, growing interest has been given to the use of miRNAs as potential biomarkers or innovative therapeutic approaches [ 6 , 21 , 22 , 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…This paper focused on hydroxymethylation in the regulation of three microRNAs (miR-155-5p, miR-326 and miR-223-3p) critically involved in the regulation of inflammatory response and neuroinflammation [8]; these microRNAs have been found to be deregulated not only in autoimmune [9] but also in neurodegenerative diseases [10]. The paper of Basak et al reported an increased level of modifications of promotors for the three miRNAs, and in particular a correlation between hydroxymethylation and the level of miR-223-3p expression in lymphocytes of MS patients compared to controls.…”
mentioning
confidence: 99%